Early outpatient clinical experience with xanomeline and trospium chloride for schizophrenia: a case report - Price, Maxwell Zachary; Price, Richard Louis (Frontiers in Psychiatry, 2025)
The combination of xanomeline, a central/peripheral muscarinic agonist, and trospium chloride, a peripheral muscarinic antagonist, (X/T) was Food and Drug Administration (FDA) approved in September 2024 for schizophrenia in adults. FDA trial subjects experiencing exacerbation or relapse of psychotic symptoms, who were neither treatment-resistant nor had taken clozapine, were tapered off previous antipsychotics, or were treatment-naive, prior to rapid X/T titration in the hospital as monotherapy. This case series addresses real-world clinical questions about how to use X/T when comorbidities with schizophrenia are the rule, polypharmacy is commonplace, and discontinuing antipsychotics prior to X/T initiation is often infeasible due to safety concerns in outpatient settings. Based on our early experience treating 40 adult outpatients with schizophrenia and comorbidities using X/T to date, we present three representative cases to share the clinical pearls we have uncovered by applying extant preclinical and clinical data. To maximize efficacy while ensuring tolerability, it is important to track cholinergic (e.g., nausea, vomiting, and diarrhea) vs. anticholinergic (e.g., gastroesophageal reflux, constipation, and urinary retention) side effects, and to adjust X/T dose, titration, administration, and concomitant medications accordingly. X/T holds potential to improve cognitive deficits in comorbid autism or dementia, warranting further study.